Pendidikan Politik untuk Meningkatkan Kesadaran Berpolitik Pemuda Melalui Pilkada Demokratis Kabupaten Kediri - Sholeh, Moh.; Setyowati, Yuni; Zubairi, Ahmad (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This program aimed to enhance the role of youth as pioneers in increasing voter participation in the regional elections (Pilkada) in Kediri Regency through political education outreach based on the Participatory Action Research (PAR) method. PAR was selected due to its emphasis on active involvement of young voters in the planning, implementation, and evaluation stages, thereby ensuring more relevant and effective outcomes. Findings from the program revealed that low political participation among youth stems from a lack of political understanding, a sense of disconnection from political processes, and general apathy. Many young people perceived no meaningful link between election results and their daily lives. During the implementation phase, outreach activities were conducted in informal settings, such as coffee shops, which proved more effective in attracting youth attention. This method succeeded in increasing young voters’ political interest and understanding, as interview results showed a positive shift in attitudes toward the significance of their role in regional elections. Interactive approaches relevant to youths' daily lives, including informal discussions and election simulations, had a significant impact on raising political awareness. Formerly apathetic youths began to recognize the importance of their voices in the local democratic process. Based on the evaluation, this model of outreach is recommended for broader application in other regions facing low youth voter turnout.